2017
DOI: 10.15640/jehd.v6n2a9
|View full text |Cite
|
Sign up to set email alerts
|

Mistake Handling Activities in Mathematics Educatıon: Practice in Class

Abstract: The purpose of the study is to examine students' ideas of mistake handling activities implemented in mathematics class. To this aim, mistake handling activities were carried out with 12 high school students. Focus group discussions related to mistake handling activities were carried out with students during four weeks. The data were gathered through students' written reflections, transcripts of focus group discussions and semi-structured interviews. All the data were analyzed through content analysis. It was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Heinze and Reiss (2007) state that handling errors can help students learn, but teachers frequently overlook this learning opportunity. Studies (Wiens, 2007;Chamundeswari, 2014;Makhubele et al, 2015;Damla Gedik et al, 2017) have indicated that one way to address the problem of students' poor achievement in Mathematics is to investigate the errors that they frequently commit in Mathematics. According to Noche (2009), the information that teachers gain from exploring errors can aid them in enhancing their instruction and assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Heinze and Reiss (2007) state that handling errors can help students learn, but teachers frequently overlook this learning opportunity. Studies (Wiens, 2007;Chamundeswari, 2014;Makhubele et al, 2015;Damla Gedik et al, 2017) have indicated that one way to address the problem of students' poor achievement in Mathematics is to investigate the errors that they frequently commit in Mathematics. According to Noche (2009), the information that teachers gain from exploring errors can aid them in enhancing their instruction and assessment.…”
Section: Introductionmentioning
confidence: 99%